Subphrenic abscess - Alburquerque Peralta, Alejandro (1970)
Subphrenic accepting classified spaces dividing them into four spaces ( two right and two left ) we call : Rights : suprahepatic and subhepótico : Left : suprahepatic lesser sac and lesser sac . In our series there were 16 Free suprahepatic abscesses (53.3 % '8 left suprahepóticos (26.6 % ' 6 subhepatic rights ( 20%) . None in the lesser sac To deal with the pathogenesis of subphrenic abscess, we have divided into two groups : Group a which corresponds to the secondary subphrenic abscesses ie all cases of subphrenic abscess that occurred as a complication of abdominal surgery (22 cases ) and group B includes all primary subphrenic abscesses ie without abdominal surgery . prior . abdominal pathology increased incidence of subphrenic abscess is the stomach and duodenum followed by the liver and extrahepatic bile ducts. subphrenic abscess the post- cpendicectomicr has ceased to be the most common cause of this type of complication. symptoms our cases are presented in relation to the location of subphrenic abscess as the subphrenic space that hosts it . Although the symptoms were mixed ( thoraco -abdominal ) , thoracic symptoms predominated in the suprahepatic abdominal abscesses and in subhepatic rights. The radiological examination showed its importance to clinical diagnosis in our cases , and was negative in one of 24 cases in which this test was performed. The hidroaérea image was present in 13 cases , the majority of them suprahepatic rights and absent in the subhepatic rights. Fluoroscopy was performed only in 8 of our case , however, in all with positive results. Surgical therapy was in most of them ( 23 cases ) and doctor in 7 cases. Of the surgically treated five patients died giving a mortality of 21.7 % and 5 treated medically died giving a mortality of 71 %. Of the 30 cases 10 died , representing an overall mortality of 33 %.